Burden and trends of major depressive disorders among women of childbearing age and the impact of the COVID-19 pandemic: insights from the global burden of disease study 2021 - Liao, Guobin; Wang, Jiaoxue; Yu, Qiaozhi; Ma, Honglin; Yan, Hezhong; He, Zhaoyun; Tang, Jun (Frontiers in Psychiatry, 2025)
BackgroundMajor depressive disorder (MDD) exhibits a pronounced female predominance, contributing substantially to disability-adjusted life-years (DALYs) among women of childbearing age (WCBA; 15–49 years). The COVID-19 pandemic intensified this burden via psychosocial stressors and disrupted healthcare access, yet integrated analyses of pre- and post-pandemic trends are scarce.MethodsLeveraging GBD 2021 data, we assessed MDD prevalence, incidence, and DALYs among WCBA globally, regionally, and nationally (1990–2021). Burden estimates were reported as point values with 95% uncertainty intervals (UIs). Temporal trends were quantified via estimated annual percentage change (EAPC) and absolute percentage change (PC). We employed autoregressive integrated moving average (ARIMA) models to compare pre-pandemic (1990–2019) and pandemic-inclusive (1990–2021) projections through 2036.ResultsGlobal prevalent cases among WCBA surged from 49.6 million (95% UI: 41.6 to 60.2) in 1990 to 85.6 million (95% UI: 70.3 to 103.8) in 2021, reflecting a 25.7% acceleration during 2019–2021 versus 1.2% annual growth pre-pandemic. Prevalence rates declined marginally pre-2019 (EAPC: −0.38, 95% CI: −0.48 to −0.29) but reversed sharply post-pandemic (EAPC: 11.47, 95% CI: −0.56 to 24.95), reaching 4,394.55 per 100,000 population in 2021. Regionally, middle and low-middle socio-demographic index (SDI) regions accounted for over 55% of global cases (23 million [95% UI: 18.9 to 27.8] and 24.2 million [95% UI: 19.6 to 29.9], respectively) in 2021, while low SDI regions showed the fastest growth (160% since 1990). High-SDI regions exhibited extremes: the highest 2021 prevalence rate (5915.76 per 100,000 population) and steepest post-2019 surge (EAPC: 13.66). In 2021, the prevalence rates were highest in high-income North America (8403.17 per 100,000 population) and lowest in East Asia (1856.99 per 100,000 population). Nationally, India reported the highest prevalent cases (16.3 million, 19% of global share), while Greenland had the highest prevalence rate (13,822.85 per 100,000 population). Adolescents (15–19 years) experienced the largest pandemic-driven increase (30.06% PC), except in East Asia where prevalence rates declined (−11.53%). ARIMA projections suggest 103.06 million global prevalent cases by 2036—32% above pre-pandemic estimates—with high SDI regions persisting at 5,617.68 per 100,000 population.ConclusionsOur analysis reveals a dual crisis: high SDI regions face entrenched high prevalence rates (5,617.68 per 100,000 population projected), while low SDI regions carry substantial burden (4,593.77 per 100,000) with rapid case expansion (160% since 1990). The pandemic disproportionately impacted adolescents globally (+30.06% PC), yet East Asia demonstrated resilience (−11.53% PC). These findings demand stratified interventions: digital mental health tools in high-income settings, community-based screening in resource-limited areas, and adolescent-focused programs worldwide. Immediate policy action is needed to avert intergenerational mental health consequences.